The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1590/s1415-47572006000200004
|View full text |Cite
|
Sign up to set email alerts
|

Optimization procedures for establishing reserve networks for biodiversity conservation taking into account population genetic structure

Abstract: Conservation genetics has been focused on the ecological and evolutionary persistence of targets (species or other intraspecific units), especially when dealing with narrow-ranged species, and no generalized solution regarding the problem of where to concentrate conservation efforts for multiple genetic targets has yet been achieved. Broadly distributed and abundant species allow the identification of evolutionary significant units, management units, phylogeographical units or other spatial patterns in genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Although methods dealing with continuous genetic variability within populations are difficult to implement, methods based on discrete genetic units are more easily handled (23). Our modularity approach defines discrete evolutionary unitsthe modules-that are amenable to incorporation in conservation planning.…”
Section: Lack Of a Spatial Segregation Of Modules And Different Roles Ofmentioning
confidence: 99%
“…Although methods dealing with continuous genetic variability within populations are difficult to implement, methods based on discrete genetic units are more easily handled (23). Our modularity approach defines discrete evolutionary unitsthe modules-that are amenable to incorporation in conservation planning.…”
Section: Lack Of a Spatial Segregation Of Modules And Different Roles Ofmentioning
confidence: 99%
“…For instance, optimization procedures can be used to find the smallest number of local populations (a network) that it is necessary to represent the species' genetic diversity (assuming, once again, that local populations were sampled throughout species' range) (Diniz-Filho & Telles 2006). This can be applied both to in situ and ex situ conservation, raising interesting possibilities for applying SCP.…”
Section: Spatial Conservation Prioritizationmentioning
confidence: 99%
“…If FBUs are defined at a very fine grain using too powerful techniques that reveal, for example, individual variation, rarity will become highly weighted and goals should be impossible to achieve. As pointed out by Diniz-Filho & Telles (2006), one can ask how to deal with population structure of these molecular variants across different species. Alternatively, genetic diversity within a species can also be a surrogate of biodiversity in general and, indeed, some recent studies have found significant correlations between genetic and species diversity (e.g., see also Sei et al 2009;Struebig et al 2011).…”
Section: Spatial Conservation Prioritizationmentioning
confidence: 99%
“…Spatial conservation prioritization, for example, has been rarely supported by assessments of local and regional genetic diversity (but see Diniz-Filho & Telles 2006). Different disciplines capable of dealing with ecological and evolutionary processes at different levels of the biological hierarchy must interact to improve conservation strategies (Diniz-Filho et al 2008).…”
Section: Applications Of Molecular Tools For Addressing Conservation mentioning
confidence: 99%